2015
DOI: 10.1021/acsami.5b03571
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Preparation of Silver Hexagonal Microsheets as Electrically Conductive Adhesive Fillers for Printed Electronics

Abstract: A facile one-step solution-phase chemical reduction method has been developed to synthesize Ag microsheets at room temperature. The morphology of Ag sheets is a regular hexagon more than 1 μm in size and about 200 nm in thickness. The hexagonal Ag microsheets possess a smoother and straighter surface compared with that of the commercial Ag micrometer-sized flakes prepared by ball milling for electrically conductive adhesives (ECAs). The function of the reagents and the formation mechanism of Ag hexagonal micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 44 publications
0
46
0
2
Order By: Relevance
“…It is also observed that pure SNP solution with an LSPR band longer than 600 nm appears blue. Interestingly, a green color which is the usual color of SNP solution 18,19,24 was absent. Actually, the green color is due to a color mixture effect of blue color representing large SNPs and yellow color representing spherical by-products which was difficult to avoid, reecting their impurity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also observed that pure SNP solution with an LSPR band longer than 600 nm appears blue. Interestingly, a green color which is the usual color of SNP solution 18,19,24 was absent. Actually, the green color is due to a color mixture effect of blue color representing large SNPs and yellow color representing spherical by-products which was difficult to avoid, reecting their impurity.…”
Section: Resultsmentioning
confidence: 99%
“…S6 † show that the thickness of SNP type III is between 10-60 nm (mean 30 nm) which is much thinner than that of previous reports. [18][19][20]22 SNPs with a size larger than 10 mm can be easily observed. A SNP with a size of $40 mm and an ultra-high aspect ratio of over 1000 : 1 was observed, as shown in Fig.…”
Section: Breaking the Size Limitation Of Snps Using Self-screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical functionalization was established by two methods: (1) the functionalization of the sizing, that was achieved by dispersing silver nanoplates into the PEI; and (2) the dispersion of silver nanowires into the matrix with CF sized with the previously mentioned functionalized sizing. To our knowledge, silver nanoplates have been only used for their optical properties, and in some rare cases as conductive filler, but never used in high performance thermoplastic matrices such as PAEK. Both mechanical and electrical properties of the different composites have been compared.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique physical and chemical properties, silver nanomaterials have attracted extensive attention in elds such as optoelectronics, [1][2][3][4] optics, 5,6 SERS, [7][8][9][10][11] conductive pastes, [12][13][14][15][16] and heaters. 17,18 It was found that morphology, size, and crystallinity strongly affect the performance of Ag nanomaterials, and great efforts have been made towards obtaining Ag nanostructures with specic morphologies such as dendrites, 19 nanowires, 20 nanorods, 21 nanocubes, 22 and nanoakes.…”
Section: Introductionmentioning
confidence: 99%